Proton Conductance at Elevated Temperature: Formulation and Investigation of Poly(4-Styrenesulfonic Acid)/4-Aminobenzylamine/Phosphoric Acid Membranes - Jalili, Jalal; Tricoli, Vincenzo (Frontiers in Energy Research, 2014)
4-Aminobenzylamine (ABA) and phosphoric acid (PA) were blended in various proportions with poly(4-styrenesulfonic acid) (PSSA) to form a new group of membranes exhibiting proton conductance under water-free conditions. The 4-ABA molecule, possessing an aniline-like and benzylamine-like functional group, can interact both with the PA and the PSSA via nucleophilic interaction, thereby allowing proton jumping in the structure. Physico-chemical and thermal characteristics of the prepared solid membranes were investigated by IR spectroscopy and thermogravimetric analysis, respectively. Electrochemical impedance spectroscopy was employed to investigate their proton-conductance properties. Transparent composite membranes were prepared. However, the membranes are opaque for relatively high content of PA. These membranes are thermally stable up to 300°C. The proton conductivity increases with temperature and also with content of PA. Values as high as 1.8 × 10−3 S cm−1 were measured at 190°C in fully anhydrous condition.